PEDAGOGICAL CHARACTERISTICS OF COLLECTIVE CREATIVE, PROFESSIONAL, AND TECHNICAL TRAINING OF FUTURE MUSIC TEACHERS (Scientific journal of the Fergana State University, 2024)
The readiness of the future music education teacher to carry out pedagogical activities is related to his knowledge, skills and qualifications, and through the acquired professional competencies, he ensures the solution of pedagogical problems that arise in the process of music education. This article describes the opinions on the modern model and professionogram of the future music teacher specialty.